Development of ternary phase diagram: optical and mechanical characterization of water/tapioca starch/triton x-100 liquid crystal - Muhd Fazreel, Muhammad Rosli (2011)
Triangle Ternary Phase Diagram can be classified as a diagram that represents the equilibrium between the various liquid crystal (LC) phases that are formed between three components. The optical and mechanical properties of ternary mixtures of Water/Tapioca Starch/Triton X-100 were studied by Polarizing Optical Microscope (POM), Simultaneous to Wide Angle X-Ray Scattering (SWAXS) and Rheometer. POM and SWAXS were used for phase identification and structure characterization. Rheometer was used to investigate the rheological properties of LC. Three different temperatures were used in this study: 15oC, 25oC and 45oC. Several texture and optical pattern were examined under the POM. The ternary phase diagram systems obtained in this work tend to form different LC phases with the increase of concentration and temperature of the mixtures. Two types of LC were formed namely Lyotropic (LLC) and Thermotropic (TLC). Lamellar and micelle phase were formed in the LLC while nematic phase was formed in TLC. Optical investigation was done by examining the change of phase in the LC according to the change of temperature and amphiphile concentration. The phase transitions of TLC was found to depend on the temperature, while for the LLC, it depends on both the temperature and concentration. SWAXS was studied with the finding of lattice spacing, d value of LC: 96.61 Angstrom for the sample 40:30:30 of Water/Tapioca Starch/Triton X-100 at 25oC as an example. The values of d are in agreement with the Bragg’s Law where the values of d increases with increasing temperature. Futhermore, the viscosity-shear rate-shear stress plot was discussed based to the rheological properties.